The relationship between teacher professional identity and burnout amid the pandemic: A moderated mediation model - Yishan Lin; Yishan Lin; Yishan Lin; Yishan Lin; Moses A. Ameyaw; Moses A. Ameyaw; Moses A. Ameyaw; Moses A. Ameyaw; Qinhan Zhang; Binghai Sun; Binghai Sun; Binghai Sun; et al. (Frontiers Media S.A., 2022)
BackgroundTeacher burnout is affected by personal and social factors. COVID-19 has greatly impacted teachers' physical and mental health, which could aggravate teacher burnout.PurposeBased on the JD-R model, this study aims to investigate the relationship between teacher professional identity (TPI) and job burnout during the COVID-19 pandemic, and examine the moderating roles of perceived organizational support (POS) and psychological resilience (PR) in these relationships among primary and secondary school teachers in China.MethodsA total of 3,147 primary and secondary school teachers participated in this study.FindingsWork engagement played a mediating role in the relationship between professional identity and burnout; when the POS and PR scores were high, the predictive coefficient of TPI on burnout was the largest.OriginalityThis study tested the mechanism underlying the relationship between TPI and burnout, and explored the protective factors of burnout.ImplicationsThis study supports the applicability of the JD-R model during COVID-19 and provides ideas for teachers to reduce burnout.